An analytical study of nano carbon materials for developing metal matrix nano composites. (2021) - Islam, Anas; Sharma, Vikas Kumar; Mausam, Kuwar
Abstract: Fast development in nanotechnology as of present days enable the development of advance metal matrix nano composites (MMNCs) for different requesting fields of building and medications like aviation, protection, automobiles, hardware, materials, science, vitality, condition, data and correspondence, purchaser products biotechnology and so forth. Carbonous material like graphite, carbon nanotubes (CNTs), carbon foams, carbon nano fibers (CNFs) and graphene are attractive reinforcement materials for self-lubricating MMNCs due to excellent electrical, mechanical and thermal properties along with lubricious nature. These materials act as solid lubricants in aluminum, titanium and magnesium MMCs for lightweight submission wherever fluid lubrication is difficult or ineffective. Besides, fluid lubricants are not ecological gracious, let go some quantities of impurity to environment. The growth of self- grease MMNCs is a significant for green or environmental gracious tribology. However, there is still some challenging problems that need to be resolved such as agglomeration of nano- size particle, low wet ability and a poor interface between particles and matrix. The results reveal that reinforcing self-lubricating carbon us materials to metal matrix decrease both coefficient of roughness and dress in rate.